A survey of massive MIMO channel measurement and model - Yanping LU; Liu LIU; Liqin FU; Jiahui QIU; Kai LIU (Dianxin kexue)
The conducted measurement campaigns at home and abroad were presented.Meanwhile, proposals and standard channel models from the international standardization organization were reviewed.The propagation characteristics of massive MIMO wireless channels were investigated based on the indoor and outdoor measurements.Moreover, the traditional and novel methods of channel modeling were analyzed.Finally, open research issues were presented.